Interfaces of 'being healthy and being Ill': how is health being perceived by individuals with non-communicable chronic conditions? - Nilanjan Bhor; P Omkar Nadh (BMC, 2024)
Abstract Background Accommodating chronic care into the everyday lives of individuals diagnosed with non-communicable chronic conditions often poses significant challenges. Several studies in public health literature that addressed the question of non-adherence to treatment by turning their gaze towards individual's perception of their own health restricted the use of perception exploration to visceral states and corporeality without adequately acknowledging the mutual permeance of socio-biological worlds. This study explored the socio-economic genealogies of individuals, to understand the role of structural and intermediate factors that determine health perceptions, by attempting to answer the question 'how do individuals with non-communicable chronic conditions perceive their health as healthy or ill'?. Methods This study was conducted in a low-income neighbourhood called Kadugondanahalli in India using qualitative research methods. A total of 20 in-depth interviews were conducted with individuals diagnosed with non-communicable chronic conditions. Individuals were recruited through purposive and snowball sampling. Results The participants predominantly perceived their health as being healthy and ill in an episodic manner while adhering to their treatment and medications for chronic conditions. This was strongly determined by the factors such as presence of family support and caregiving, changes in work and occupation, changes in lifestyle, psychological stress from being diagnosed, and care-seeking practices. This episodic perception of illness led to the non-adherence of prescribed chronic care. Conclusions Due to the episodic manner in which the participants experienced their illness, the paper recommends considering health and illness as two different entities while researching chronic conditions. It is important for the health system to understand and fix the healthy and ill episodes, which often lead to switching between controlled and uncontrolled states of diabetes and hypertension. To do so, it is important to consider the social, economic, behavioural and psychological factors in an individual's health outcome. The interplay between these factors has socialized health perception and various related practices from the individual to the community level. Therefore, the health system needs to re-strategize its focus from individual to community level interventions to address the determinants of health and NCD risk factors by strengthening the NCD prevention approach.